Gingival Overgrowth Leading to the Diagnosis of Familial Tuberous Sclerosis Complex. (13th January 2016) - Purwar, Parth; Sareen, Sagar; Sheel, Vaibhav; Gupta, Abhishek; Ansari, Uzma; Becharbhai, Patel Umeshbhai; Dixit, Manisha; Bhargava, Amitesh; Yadav, Rajiv Ratan Singh; Bansal, Utkarsh; Dixit, Jaya
Abstract : Tuberous sclerosis complex (TSC), a neurocutaneous syndrome, is characterized by the development of benign tumours affecting different body systems. We herein present a report of a 40-year-old female patient presenting with dental enamel pits and localized gingival overgrowth that eventually lead to the diagnosis of a case of familial TSC. Diagnosis of familial TSC by comprehensive oral examination and detection of oral manifestations proved to be inevitable as it resulted in institution of appropriate treatment strategies and genetic counselling of the affected family.